Depresión y su influencia en la conducta de una adolescente de 14 años - Moreira Vera, Diana Carolina (2020)
Depression is one of the mood disorders in which symptoms of irritability, sadness, apathy, anhedonia predominates, generating a great negative impact on the development of the cognitive, volitional, physical adolescent, being considered one of the main factors of risk of suicide and one of the most disabling mental illnesses in psychosocial functioning. The present work is a practical case study, a prerequisite for obtaining the title of Clinical Psychologist in the complex examination modality whose line of research is psychological counseling whose subject is depression and its influence on the behavior of an adolescent from 14 years with the general objective of identifying the symptoms of depression and how it influences the behavior of a 14-year-old adolescent in which the signs and symptoms of the problem were evaluated through techniques and psychological tools such as the clinical interview, observation, Clinical history and psychological tests such as Beck's BDI depression test, self-control scale test, projective tests such as HTP detected the findings in the emotional, cognitive, physiological and behavioral areas, facilitating the framing of the presumptive moderate depressive episode diagnosis and the development of the scheme therapeutic with the cognitive behavioral approach using restructuring techniques Cognitive training, relaxation training, self-control therapy in order to decrease symptoms, dysfunctional thoughts, modeling of their behavior and to improve their self-control skills.